MANAGEMENT’S DISCUSSION AND ANALYSIS ON MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2011 - 2014 - Ongkoseputro, Marina Fabiola (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2019)
The study aims to examine the information contained in the Management’s Discussion and Analysis (MD&A) on manufacturing companies listed in Indonesia Stock Exchange period 2011 to 2014. The content of information that will influence the market reaction is proxied by stock returns and trading volume activity. The object of research is manufacturing companies listed in Indonesia Stock Exchange period 2011 to 2014. The number of samples per year are 84 companies so that the observed total company became 336, selected using purposive sampling technique. The hypothesis was tested using non-parametric test partial correlation and multiple linear regression analysis using the control variable is return on equity. The result showed that the disclosure in the annual MD&A report positive effect on stocks returns was rejected. This can be caused by an Indonesian company is not ready to face the disclosure in the annual report as well as the state of efficiency of the Indonesian market is still relatively strong spring. The second hypothesis stated unsupported because there is a positive correlation MD&A disclosure in the annual report of the trading volume activity. Thus, the relationship between the publication of information both annual reports, social conditions and socio-political circumstances that affect the company against fluctuations in trading volume activity.